(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In past few years, as tourism has grown in popularity throughout the globe, a greater emphasis has been placed on countryside tourism. Countryside tourism is now the centre of interest all across the globe and it is increasingly identified as a crucial driver of rural economic development. Tourism is the 2nd highest revenue-giving sector in the world, behind the oil industry. As a result, the nation must distinguish between various kinds of visitors in order to comprehend and analyze the purpose of their presence. As a result, rural tourism has a lot of promise and may generate a lot of money in the near future. The primary goal of this article is to investigate the advantages and drawbacks of rural tourism in Orissa. The nature of this work is descriptive. The comprehensive research approach was used to continue this study and to determine the goals. Research papers, accessible literary materials, scholarly publications, cases, and other published and unpublished resources on the subject were used to gather pertinent and supporting data. According to the research, rural tourism or eco-tourism, if professionally organized, promoted, and administered, may enhance the living conditions of the local people while also helping the protection of the natural environment. While tourism has evolved as a burgeoning sector in Orissa, the issue now is to maximize the benefits of the scenario by making the most use of the natural resources available.